2002
DOI: 10.1086/340615
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Leptospirosis among Triathlon Participants and Community Residents in Springfield, Illinois, 1998

Abstract: We investigated an outbreak of leptospirosis among athletes and community residents after a triathlon was held in Springfield, Illinois. A telephone survey was conducted to collect clinical information and data on possible risk factors, community surveillance was established, and animal specimens and lake water samples were collected to determine the source of the leptospiral contamination. A total of 834 of 876 triathletes were contacted; 98 (12%) reported being ill. Serum samples obtained from 474 athletes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
167
1
23

Year Published

2004
2004
2009
2009

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 239 publications
(200 citation statements)
references
References 15 publications
(16 reference statements)
9
167
1
23
Order By: Relevance
“…Analysis during the outbreak investigation demonstrated that swallowing water was significantly associated with seropositivity among the full race cohort; 16 however, in our study, there was no difference in the proportion reporting a history of swallowing water among laboratory-confirmed cases (18/27, 67%) and controls (30/44, 68%). Table 1 shows the distribution of TNF-a À308 promoter alleles and HLA-DR genotypes.…”
Section: Resultscontrasting
confidence: 87%
See 2 more Smart Citations
“…Analysis during the outbreak investigation demonstrated that swallowing water was significantly associated with seropositivity among the full race cohort; 16 however, in our study, there was no difference in the proportion reporting a history of swallowing water among laboratory-confirmed cases (18/27, 67%) and controls (30/44, 68%). Table 1 shows the distribution of TNF-a À308 promoter alleles and HLA-DR genotypes.…”
Section: Resultscontrasting
confidence: 87%
“…Most study subjects were homozygous TNF1 or heterozygous at this site; two individuals were TNF2 homozygous (Datasheets A and D, see Supplementary Information). In all, 13 HLA-DR genotypes 1,3,4,[7][8][9][10][11][12][13][14][15][16] were identified within this cohort; the HLA-DR genotype was unambiguous for all 85 specimens. Bivariate analysis of laboratory-confirmed cases showed no TNF-a polymorphism or HLA-DR genotype significantly associated with case-status (Data-sheets A and D, see Supplementary Information).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The MAT is not serovar-specific, but the 7 serovars evaluated in this study belong to different serogroups ( 13 ). Serovar Grippotyphosa, the second most common positive serovar in this study, has also been associated with human leptospirosis outbreaks in the 1990s ( 8 ). …”
Section: Discussionmentioning
confidence: 64%
“…Case reports have attributed canine infection primarily to serovars Grippotyphosa, Pomona, Bratislava, and Autumnalis ( 4 6 ). Although human leptospirosis ceased to be a notifiable disease in 1994, outbreaks are still reported and infecting serovars in humans are antigenically related to the emerging serovars in dogs ( 7 , 8 ). …”
mentioning
confidence: 99%